Fish Fillet: White Versus Red, Structure and Nutritional Composition - Rose Omidvar; Michael Sipos; Razieh Farzad (EDIS, 2024)
Fish is one of the primary sources of protein and other nutrients globally. There are thousands of food fish species with different chemical compositions and nutritional characteristics of fillets. Therefore, this EDIS publication has provided information on fish muscle structure and differences between red muscles and white muscles in fish. In addition, discussions on fish muscle composition and the effect of the heat on the muscle are provided.